2013
DOI: 10.1002/psc.2489
|View full text |Cite
|
Sign up to set email alerts
|

Peptide inhibitors against herpes simplex virus infections

Abstract: Herpes simplex virus (HSV) is a significant human pathogen causing mucocutaneous lesions primarily in the oral or genital mucosa. Although acyclovir (ACV) and related nucleoside analogs provide successful treatment, HSV remains highly prevalent worldwide and is a major cofactor for the spread of human immunodeficiency virus. Encephalitis, meningitis, and blinding keratitis are among the most severe diseases caused by HSV. ACV resistance poses an important problem for immunocompromised patients and highlights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 129 publications
(160 reference statements)
1
52
1
Order By: Relevance
“…Considering that treatment with AMPs is potentially effective and non-toxic to humans and animals, it has already been proposed as an alternative for disease control (Galdiero et al, 2013). According to Al-Khayat and Ahmad (2012) if TI is one or less, the drug has significant side effects, but if the index is larger than one, the margin of safety is large.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that treatment with AMPs is potentially effective and non-toxic to humans and animals, it has already been proposed as an alternative for disease control (Galdiero et al, 2013). According to Al-Khayat and Ahmad (2012) if TI is one or less, the drug has significant side effects, but if the index is larger than one, the margin of safety is large.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of human herpesviruses (HHV) to acyclovir has been widely reported and cidofovir and foscarnet -the other two drugs usually used for HHV therapy -are both nephrotoxic and their use restricted to confirmed cases of acyclovir resistance (GALDIERO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, antimicrobial peptides can exert a broad spectrum of activity on infectious agents; they can be highly specific and effective and even biodegraded by peptidases, which limit their accumulation and results in lower toxicity (GALDIERO et al, 2013). Several reports have shown the antiviral potential of synthetic and naturally occurring peptides against different viruses such as HHV-1 and HHV-2, human immunodeficiency virus (HIV), vesicular stomatitis virus (VSV), influenza A virus, cytomegalovirus, adenovirus, rotavirus and other viruses (DAHER et al, 1986;CARRIEL-GOMES et al, 2007;BASU et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…10,11) In addition, n-docosanol (Abreva) is another fusion inhibitor that has been approved by the Food and Drug Administration (FDA) and marketed for the treatment of recurrent herpes simplex labialis. 12,13) In recent years, it has also been shown that antimicrobial peptides (AMP), 14) or other synthetic peptides that bind to 3-OS HS exhibited anti-HSV-1 effects during HSV-1 infection in vivo. 15,16) The use of peptides has several advantages compared with chemical compounds; they can exert a broad spectrum of activity on different microorganisms, and they are highly specific and effective.…”
mentioning
confidence: 99%